2016
DOI: 10.19173/irrodl.v17i5.2456
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Cognitive Engagement in Online Discussion: Use of a Scaffolded, Audio-based Argumentation Activity

Abstract: The purpose of this paper is to explore how adult learners engage in asynchronous online discussion through the implementation of an audio-based argumentation activity. The study designed scaffolded audio-based argumentation activities to promote students' cognitive engagement. The research was conducted in an online graduate course at a liberal arts university. Primary data sources were learners' text-based discussions, audio-recorded argumentation postings, and semi-structured interviews. Findings indicate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…The quantitative results of social presence and teaching presence questionnaires also indicated that the participants who utilized the video-enhanced platform for the course discussion activities demonstrated higher perceptions of social and teaching presence than those using the text-based ODB. Oh and Kim (2016) contended that learners can only achieve higher-order thinking skills when they actually make cognitive efforts to engage deeply in online discussions. They designed scaffolded audio-based discussion activities using VoiceThread to promote students' cognitive engagement and perceived experiences.…”
Section: Technology Utilization For Online Discussionmentioning
confidence: 99%
“…The quantitative results of social presence and teaching presence questionnaires also indicated that the participants who utilized the video-enhanced platform for the course discussion activities demonstrated higher perceptions of social and teaching presence than those using the text-based ODB. Oh and Kim (2016) contended that learners can only achieve higher-order thinking skills when they actually make cognitive efforts to engage deeply in online discussions. They designed scaffolded audio-based discussion activities using VoiceThread to promote students' cognitive engagement and perceived experiences.…”
Section: Technology Utilization For Online Discussionmentioning
confidence: 99%
“…Students' broader circumstances, such as employment commitments, family responsibilities, and support, have also been associated with academic success, satisfaction, and online student attrition (Creed et al, 2015;Moore & Greenland, 2017;Palmer et al, 2011). In addition, interaction with instructors, content, and peers has been found to contribute to online students' learning, performance, satisfaction, and retention (Bawa, 2016;Bourdeaux & Schoenack, 2016;Garratt-Reed et al, 2016;Oh & Kim, 2016). Curriculum challenge, flexibility, and relevance have been linked to student satisfaction and retention (Bradford, 2011;Su & Waugh, 2018); and technical difficulties can contribute to students' dissatisfaction and attrition (Bawa, 2016;Ilgaz & Gulbahar, 2015).…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…Meaningful interaction with peers and instructors, dynamic and engaging learning activities, and the application of innovative technology should be actively encouraged (Stone, 2017;Tomas et al, 2015). Instructors who are accessible and responsive (Stone & O'Shea, 2019), facilitation of opportunities for meaningful peer interaction (Oh & Kim, 2016), use of a variety of dynamic materials and strategies to engage students (Bourdeaux & Schoenack, 2016), and encouraging the application of learning beyond the course (Sansone et al, 2012), may facilitate a more positive OSE.…”
Section: Implications For Oe Policy and Practicementioning
confidence: 99%
“…Differentiated coding schemes. Despite a clear majority of the studies utilizing the PIM as a coding scheme (11 of 16), there were a number that employed different models for assessing critical thinking (Curtis, 2006;Darabi et al, 2011;Hand, 2015;Oh & Kim, 2016;Yang et al, 2005). Therefore, it is possible that the reasons for, and descriptions of, the coding schemes provided by these researchers may reveal potential shortcomings within the PIM.…”
Section: Modelling Effective Discoursementioning
confidence: 99%